The reliability of the Shuttle Walking Test, the Swiss Spinal Stenosis Questionnaire, the Oxford Spinal Stenosis Score, and the Oswestry Disability Index in the assessment of patients with lumbar spinal stenosis. - Pratt, R; Fairbank, J; Virr, A (2002)
STUDY DESIGN: The Shuttle Walking Test (SWT), the Swiss Spinal Stenosis (SSS) Questionnaire, the Oxford Claudication Score (OCS), and the Oswestry Disability Index (ODI) were administered to patients with lumbar spinal stenosis and neurogenic claudication. OBJECTIVE: To determine reliability of the SWT, the SSS (Q1-12), the OCS, and the ODI in lumbar spinal stenosis assessment. SUMMARY OF BACKGROUND DATA: Reliability data for exercise tests in lumbar spinal stenosis are lacking. METHODS: To determine reliability, 32 clinic patients with lumbar spinal stenosis were assessed twice, with 1 week between assessments. Retrospective data from 17 patients assessed before surgery and 18 months after surgery for lumbar spinal stenosis were used to investigate the use of reliability in a clinical setting. RESULTS: Test-retest reliability in terms of the intraclass correlation coefficient (ICC) was 0.92 for the SWT, 0.92 for the SSS, 0.83 for the OCS and 0.89 for the ODI. The mean percentage scores were 51 for the SSS, 45 for the OCS, and 40 for the ODI. To achieve 95% certainty of change between assessments for a single patient, the SSS would need to change by 15, the OCS by 20, and the ODI by 16. The mean SWT was 150 m, with a change of 76 m required for 95% confidence. Cronbach's alpha was 0.91 for the SSS, 0.90 for the OCS, and 0.89 for the ODI. The change in ODI correlated most strongly with patient satisfaction after surgery (rho = 0.80; P < 0.001). CONCLUSIONS: Fluctuations in a patient's symptoms result in wide individual confidence intervals. Performance on the SSS, OCS, and ODI questionnaires are broadly similar, the most precise being the condition-specific SSS. The SWT gives a snapshot of physical function, which is acceptable for group analysis. Use of the SWT for individual assessment after surgery is feasible.